2022
DOI: 10.1101/2022.03.06.483167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of paclitaxel treatment on cellular mechanics and morphology of human oesophageal squamous cell carcinoma in 2D and 3D environments

Abstract: During chemotherapy, structural and mechanical changes in malignant cells have been observed in several cancers, including leukaemia, pancreatic and prostate cancer. Such cellular changes may act as physical biomarkers for chemoresistance and cancer recurrence. This study aimed to determine how exposure to paclitaxel affects the intracellular stiffness of human oesophageal cancer of South African origin in vitro. A human oesophageal squamous cell carcinoma cell line WHCO1 was cultured on glass substrates (2D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, cell mechanics is also affected by many of the cancer drugs in the market, specifically targeting elements of the cytoskeleton and membrane of cells. Examples of these drugs are Doxorubicin (membrane peroxidation), 81,148 Taxol (tubulin depolymerization suppression), 149,150 Dexamethasone (actin filaments reorganization), 151,152 and Vincristine or Vinblastine (microtubules polymerization suppression) 83,153 . However, they present important secondary effects like cardiotoxicity, thus novel drugs targeting the cytoskeletal structures are being studied for clinical use.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cell mechanics is also affected by many of the cancer drugs in the market, specifically targeting elements of the cytoskeleton and membrane of cells. Examples of these drugs are Doxorubicin (membrane peroxidation), 81,148 Taxol (tubulin depolymerization suppression), 149,150 Dexamethasone (actin filaments reorganization), 151,152 and Vincristine or Vinblastine (microtubules polymerization suppression) 83,153 . However, they present important secondary effects like cardiotoxicity, thus novel drugs targeting the cytoskeletal structures are being studied for clinical use.…”
Section: Cancermentioning
confidence: 99%
“…Studies demonstrated that filamentous structures can change their mechanical properties in fast biochemical processes like phosphorylation, ion concentration, and associated protein interactions. 41,42,46 depolymerization suppression), 149,150 Dexamethasone (actin filaments reorganization), 151,152 and Vincristine or Vinblastine (microtubules polymerization suppression). 83,153 However, they present important secondary effects like cardiotoxicity, thus novel drugs targeting the cytoskeletal structures are being studied for clinical use.…”
Section: Cancermentioning
confidence: 99%
“…The use of small molecules targeting cytoskeleton de-/polymerization has proven useful for elucidating the role of the cytoskeleton in the regulation of cell shape and mechanical properties underpinning cell lineage specification 1 . Paclitaxel (PAX) inhibits tubulin depolymerization, thus stabilizing microtubules, increasing microtubule bundling, and leading to an increase in cell stiffness 6 . F-actin and tubulin act in concert and exhibit compensatory effects in the cell; hence, inhibition of microtubule depolymerization with PAX is accompanied by significant changes in Factin, resulting in dose-dependent decreases in MSC migratory capacity and differentiation potential 7 .…”
mentioning
confidence: 99%